Skills and practices of pharmacy staff for dispensing of drugs with fiscalized substances in drugstores and pharmacies - Mauricio Ceballos; Yaqueline Llano; Andrea Salazar-Ospina; Juliana Madrigal-Cadavid; Daniel Pino-Marín; Pedro Amariles (Universidade de São Paulo, 2021)
ABSTRACT OBJETIVE To evaluate the skills and practices of pharmacy staff during the dispensing of tramadol (drug with fiscalized substance) in drugstores and pharmacies in Medellin, Colombia. METHODS A cross-sectional study was performed. The simulated patient technique was used. The main outcomes included the information provided on the dispensed drug (tramadol), the use of tools to provide information, and the information provided on drug precautions and use recommendations. RESULTS We visited 305 drugstores and pharmacies. The average dispensing time was 2.3 min (SD 1.1 min). In nine drugstores and pharmacies (3.0%), tramadol was not dispensed because it was not in stock. In 17 drugstores and pharmacies (5.7%), the simulated patients were actively informed by the dispensing pharmacy staff; of these, 16 provided oral information and one provided oral and written information. Eight patients (2.7%) received information regarding tramadol use. However, 99% of patients were not informed about tramadol side effects such as dependence, sedation, or hypnosis, and none of the simulated female patients were informed on the precautions related to tramadol use during pregnancy or lactation. CONCLUSIONS Communication skills and appropriate practices of pharmacy staff are critical to patient self-care. However, this study shows their difficulty in counseling about precautions and use recommendations of drugs with fiscalized substances. These outcomes could inform future studies focusing on the rational use of these drugs in drugstores and pharmacies. It is necessary to improve the pharmacy staff competencies through continuing education programs, to facilitate access to information and training.